MEMBANGUN KESETARAAN MELALUI PENDIDIKAN INKLUSIF: PERAN SEKOLAH DASAR DI GEMOLONG - Rindu Nur Cahyati; Kayla Hajar Zahira; Vita Nabila; Minsih (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2025)
Inclusive education is an approach that guarantees the fulfillment of educational rights for all students, including Children with Special Needs. This research aims to describe the role of inclusive education in building equality for children with special needs and the school's role in supporting this equality. The research method used a qualitative descriptive approach with data collection techniques in the form of non-participation observation and semi-structured interviews at SD Aisyiyah Unggulan Gemolong. The results showed that the implementation of inclusive education in the school involved the roles of the principal, classroom teachers, and special education teachers in facilitating the development of children with special needs. The principal acts as a leader, manager, educator, and supervisor; classroom teachers implement adaptive learning methods; while special education teachers provide assistance services 2-3 times a week. This research concludes that despite facing challenges of limited resources and infrastructure, collaboration between the principal, classroom teachers, and special education teachers can create an equal educational environment. This collaborative model offers a practical approach that can be adapted by other elementary schools in implementing inclusive education, while contributing to the development of more effective inclusive education strategies in Indonesia.